O systemie konceptualnym i realizmie zewnętrznym - Muszyński, Zbysław (Filozofia Nauki, 2003)
The notion of conceptual system is usually connected with criticism or defence of relativism but sometimes the notion appears in discussion on realism/anti-realism. The aim of the article is: (1) to present connection between understanding of notion of conceptual system and ways of understanding of realism/anti-realism; (2) to present that notion may constitute a foundation of argument for realism, although usually it is taken as argument for anti-realism. Investigations of the article create the basis for discussion of the conception of relativity proposed by Adam Grobler in Truth and Relativity.